Estudo do efeito da angiotensina 1-7 em um modelo de fibrose pulmonar induzida por bleomicina - Flavia Rago Glória Gonçalves (2017)
Bleomycin - induced lung toxicity is a collateral effect commonly developed by patients submitted to chemotherapy treatments, causing dyspnea, hypoxia and decreased lung capacity, leading patients to death. Bleomycin is an antineoplastic agent used to treat a huge range of lymphomas, head and neck cancer, ovarium and testicular cancer, which has 90% of cure. However, bleomycin therapeutic efficacy is limited because it can mediate both single-stranded and double-stranded DNA damage, and consequently lung fibrosis. That is why the study of strategies that minimize the effect of treatment with this drug is necessary. We have studied the effect of the previous treatment with angiotensin 1-7 on bleomycin-induced lung fibrosis model. Angiotensin 1-7 is a heptapeptide of renin-angiotensin system, with anti-fibrotic and anti-inflammatory activity, and it has been studied in some models of lung fibrosis. Due to this, we aim to study the inflammatory and fibrotic parameters on Bleomycin-induced lung fibrosis of mice under the treatment with angiotensin 1-7, via gavage. First, we standardized a dose of bleomycin to be used in our model. After this, male mice C57Bl/6j were treated with angiotensin 1-7, one hour before the induction of lung fibrosis. The animals were euthanized 2, 7 and 14 days after bleomycin instillation. We observed that the pre-treatment with angiotensin -17 decreased the animals weight lost and increased the animal’s life time. The treatment also decreased, significantly, the levels of mononuclear cells and neutrophils in the mice airways, as well as the levels of neutrophil in lung tissue. Therefore, our results indicate that the pre-treatment with angiotensin 1-7, in this Bleomycin-induced lung fibrosis model, improves inflammatory process in the airways and lung tissue of mice treated, increasing their life time.